Inherited Platelet δ-Storage Pool Disease in Dogs Causing Severe Bleeding: An Animal Model for a Specific ADP Deficiency - Callan, Mary Beth; Bennett, Joel S; Phillips, Deborah K; Haskins, Mark E; Hayden, James E; Anderson, Jamie G; Giger, Urs (Thrombosis and Haemostasis, 1995)
The nature of a disorder producing moderate to severe bleeding after minor trauma, venipuncture, and surgery was studied in 3 families of American cocker spaniel dogs. In the 5 affected dogs tested, platelet counts and measurements of plasma coagulant function and von Willcbrand factor were normal. However, bleeding times were prolonged in 4 of the 5 affected dogs tested, and platelet aggregation in response to ADP and collagen was consistently abnormal in 3, suggesting that the bleeding disorder was due to abnormal platelet function. Measurements of 14C-serotonin uptake and retention by the affected platelets were normal. However, their ADP content was decreased, while their ATP content was normal, resulting in a mean ATP/ADP ratio of 8.32, compared to a mean ratio of 1.9 in normal canine platelets. Electron microscopy revealed that the number and appearance of the dense granules in the affected platelets were indistinguishable from those of normal controls. These studies suggest that this bleeding disorder results from a deficient δ-granule storage pool of ADP; given the normal serotonin uptake and retention by affected platelets and the apparently normal number of dense granules, the ADP deficiency may be the consequence of a selective defect in δ-granule ADP transport. Additional studies of this unique platelet disorder will provide an opportunity to understand the mechanism of adenine nucleotide storage in platelet δ granules.